Hak Eksekutorial Lembaga Perkreditan Desa Terhadap Benda Jaminan Hak Tanggungan yang Berkedudukan di Luar Wilayah Desa Adat - I Putu Yoga Eka Putra Gunawan; I Nyoman Putu Budiartha; Ni Made Puspasutari Ujianti (Jurnal Analogi Hukum, 2021)
LPD is a financial institution belonging to the Traditional Village which is domiciled in the authority of the Traditional Village. Furthermore, the following issues will be discussed: (1)How is the Regulation of Village Credit Institutions as Traditional Village Financial Institutions in Bali, (2)How is the Existence of Village Credit Institutions Against Mortgage Guaranteed Objects Located Outside the Traditional Village. The research method is normative and the type of approach This problem consists of a statutory approach and a conceptual approach. The sources of legal materials used are primary legal materials in the form of laws and regulations. Legal Materials Collection Techniques through documentation study techniques and literature studies. peeling of lawful Materials through depiction, interpretation and argument techniques. A conclusion thesis is valid according to the rules of Article 5 paragraph (1) Governor Regulation No. 44 of 2017 and Law Number 4 of 1996 provide for validity of the LPD's execution which gives the authority to the first party to keep an auction so that it carries the purpose of pawn on its own strength.